Korzystanie przez kobiety z porad lekarza ginekologa - Słopiecka, Aleksandra (Nursing Problems / Problemy Pielęgniarstwa, 2013)
Introduction. Little interest of women in prophylactic examination and their low readiness to use the advice of gynaecologists is an obstacle in obtaining a major decrease in mortality of Polish women resulting from neoplastic diseases of the reproductive organ. Aim. The object of the paper was an analysis of women’s attitudes towards the use of a gynaecologist’s advice. Material and methods. Qualified for the research were 210 women aged 18 to 73. The respondents were hospitalized for the need to diagnose and/or treat diseases within their reproductive organ. The field of the research was the four gynaecological departments functioning in hospitals in the city of Kielce. In the research the method of diagnostic poll and the analysis of documents were used. The questionnaire prepared by the author and Health Information Form were used as the research tools. Results. For most respondents (69.5%) their first visit to a gynaecologist took place when they were pregnant. 41.9% of the women visited a gynaecologist regularly, i.e. at least once a year. Among those who visited a gynaecologist sporadically nearly 88 % explained their behaviour using the argument “I felt healthy and I did not see the need”. Conclusions. 1. The majority of respondents (69.5%) to the time of pregnancy has not benefited from gynaecologist’s advice 2. The vast majority of respondents (87.7% of the analysed group) to the time of pregnancy has not benefited from gynaecologist’s advice. 3. The level of education and place of residence in a statistically significant way differentiated the behaviour of women in the use of gynecologist advice. Nursing Topics 2013; 21 (1): 47–54